Estimating the Fraction of First-Year Hemodialysis Deaths Attributable to Potentially Modifiable Risk Factors: Results from the DOPPS - Karaboyas, Angelo (Clin Epidemiol, 2020)
PURPOSE: Mortality among first-year hemodialysis (HD) patients remains unacceptably high. To address this problem, we estimate the proportions of early HD deaths that are potentially preventable by modifying known risk factors. METHODS: We included 15,891 HD patients (within 60 days of starting HD) from 21 countries in the Dialysis Outcomes and Practice Patterns Study (1996–2015), a prospective cohort study. Using Cox regression adjusted for potential confounders, we estimated the fraction of first-year deaths attributable to one or more of twelve modifiable risk factors (the population attributable fraction, AF) identified from the published literature by comparing predicted survival based on risk factors observed vs counterfactually set to reference levels. RESULTS: The highest AFs were for catheter use (22%), albumin <3.5 g/dL (19%), and creatinine <6 mg/dL (12%). AFs were 5%-9% for no pre-HD nephrology care, no residual urine volume, systolic blood pressure <130 or ≥160 mm Hg, phosphorus <3.5 or ≥5.5 mg/dL, hemoglobin <10 or ≥12 g/dL, and white blood cell count >10,000/μL. AFs for ferritin, calcium, and PTH were <3%. Overall, 65% (95% CI: 59%-71%) of deaths were attributable to these 12 risk factors. Additionally, the AF for C-reactive protein >10 mg/L was 21% in facilities where it was routinely measured. CONCLUSION: A substantial proportion of first-year HD deaths could be prevented by successfully modifying a few risk factors. Highest priorities should be decreasing catheter use and limiting malnutrition/inflammation whenever possible.